Substantial Aspects and its Relationship with the Research Results of Lecturers - Sudiana, I Ketut; Sugiarta, Made; Sastrawidana, Ketut; Erlina, Nia (Journal of Education Reseach and Evaluation, 2023)
Based on the eight focus areas of educational research, it is necessary to support clear information on evidence based on the focus areas contained in the strategic research plan of the Ganesha University of Education. This study aims to analyze and describe the substance aspects and the relationship with the research results of lecturers at Undiksha. This research is a type of ex-post facto research with meta-analysis. The subjects of this research were all Undiksha lecturers and functional staff. The objects of this research are research schemes, fields of knowledge, research road maps, vision and mission, and lecturer expertise in research. Data collection techniques are observation, documentation, and response questionnaires. The results of the research show that (1) the need for lecturer knowledge regarding the basis for the preparation of the research road map. There is research with the qualification that 30.06% include an appropriate road map, 6.19% include an inappropriate road map, and 63.75% do not contain a road map. (2) Existing research is appropriate and supports the vision and mission of LPPM Undiksha. (3) Expertise and interest underlie the mapping of research groups in each study program. As much as 93.3% of the lecturer's research was on the need for study program development. The results of this study serve as basic support in developing sustainability designs in research for lecturers and the basis for forming research groups.